The Urgency of Personal Communication Skills and Teacher Discipline on Student Learning Motivation - Yusmeini, Dinda; Indriani, Friska; Cintia; Basir, Faisal (Journal of General Education Science, 2023)
The teaching and learning process is essentially a communication process, namely the process of conveying messages from news sources to message recipients through certain channels/media. There is a need for diverse teacher roles in relation to their roles as teachers, educators and mentors. The role of a teacher is always to describe the expected patterns of behavior in his interactions with students (among others), fellow teachers, and other staff. Communication must occur in the learning process. Communication is so important in the learning process that it is impossible to imagine what the learning process would be like without communication. Teachers provide learning materials in class for students to discuss and create materials, or teachers and students discuss topics together. This is a communicative activity that occurs during learning. When studying communication, what to say and how to say it are two important things. As social creatures, humans cannot escape communication, both verbal and non-verbal, because in the learning process there must be a communication process. between educators and students. So student learning motivation will be directly proportional to the teacher's interpersonal communication skills and this means that the teacher's interpersonal communication has a direct effect on student learning motivation.